Modelación de erosión hídrica en los cantones de calvas, chaguarpamba y Saraguro mediante sistemas de información geografíca y teledetección. - Sanmartín Pucha, Edwin Fabián (2017)
Soil erosion affects the entire world mainly causing its degradation. The objective of this study is to estimate soil erosion using the revised universal soil loss equation (RUSLE) and to evaluate soil conservation practices in Calvas, Chaguarpamba and Saraguro cantons of the province of Loja. For this purpose, precipitation, soils, vegetation cover, slope length and conservation practices were collected to determine RUSLE factors. The results that were obtained, Calvas canton shows a high soil loss between 50-200 t ha-1 year -1 (28.38% of the canton) and a very high soil loss> 200 t ha-1 year -1 (7 , 30% of the canton), Chaguarpamba canton has a high soil loss between 50-200 t ha-1 year -1 (0.6% of the canton) and a very high soil loss> 200 t ha-1 year -1 (1.4% of the canton), and Saraguro canton has a high ground loss between 50-200 t ha-1 year -1 (2.46% of the canton) and a very high ground loss> 200 t ha-1 year -1 (1.1% of the canton). Therefore, to reduce erosion, good agricultural practices have to be implemented, such as reforestation in Calvas, reducing 8.9% of soil loss> 50 t ha-1 year -1, crops to contour lines in Chaguarpamba reducing 0 , 3% soil loss> 50 t ha-1 year -1, slash-and-burn crops in Saraguro reducing 1.61% soil loss> 50 t ha-1 year -1.